2013
DOI: 10.1016/j.ajpath.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length and Fragmented Netrin-1 in Multiple Sclerosis Plaques Are Inhibitors of Oligodendrocyte Precursor Cell Migration

Abstract: Oligodendrocytes exhibit a limited capacity to remyelinate in multiple sclerosis. Factors present in multiple sclerosis lesions are thought to inhibit oligodendrocyte precursor cell migration, limiting their recruitment to axons requiring remyelination; however, few inhibitors have been identified. A candidate inhibitor is netrin-1, a secreted protein that repels migrating oligodendrocyte precursor cells during neural development and is expressed by myelinating oligodendrocytes in the mature rodent central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
2
28
1
2
Order By: Relevance
“…The specificity of the antibody used on human tissue was previously established. 9 Axons were present in all lesions analyzed (see Fig 1B). In NAWM, the netrin- Fig 1S-U) and Unc5A (see Fig 1V-X) expression was detected, indicating potential chemotropic influence of netrin-1 on adult human OPCs.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The specificity of the antibody used on human tissue was previously established. 9 Axons were present in all lesions analyzed (see Fig 1B). In NAWM, the netrin- Fig 1S-U) and Unc5A (see Fig 1V-X) expression was detected, indicating potential chemotropic influence of netrin-1 on adult human OPCs.…”
Section: Resultsmentioning
confidence: 74%
“…28,29 It has recently been shown that full-length netrin-1 protein and fragments of netrin-1 are found in chronic MS lesions. 9 In addition, netrin-1 has been shown to induce blood vessel remodeling in the subventricular zone following demyelination of the corpus callosum, which allowed for neuroblast emigration toward the lesion. 30 However, the role of netrin-1 in myelin repair remains uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While full-length netrin-1 has vasoprotective properties (21) and maintains blood-brain barrier function (45), the newly generated fragments contribute to the breakdown of the BRB and thus exacerbate retinal and macular edema. A role for the VI-V fragment of netrin-1 in pathology was previously suggested, given its presence in multiple sclerosis (MS) plaques and capacity to inhibit oligodendrocyte migration (46). While netrin-1 is required for the maintenance of axo-oligodendroglial paranodal junctions (47), ectopic expression of netrin-1 in vivo inhibited remyelination in an experimental model of MS lesions (48).…”
Section: Inhibition Of Collagenases or Mmp-9 In Vivo Reduces Pathologmentioning
confidence: 99%
“…Netrin-1 is a matrix-bound molecule interacting with different receptors (UNC and DCC, certain integrins, DSCAM -Down's syndrome cell adhesion molecule and adenosine receptor AR2b) involved in axon guidance and angiogenic blood vessel guidance [reviewed in 91], that has been shown to inhibit migration of oligodendrocyte precursor cells into the demyelinated lesions [129]. Ephrins and their Eph receptors are short range axon guidance molecules, expressed in developing vessels and critical for their maintenance [reviewed in 91], that have shown different expression profiles in several CNS cytotypes of MS patients [130].…”
Section: Other Angiogenic Molecules Potentially Involved In Ms and Eamentioning
confidence: 99%